Research note: Machinery, manumission, and economic machinations - Edwards, D.; Pärn, E.; Love, Peter; El-Gohary, H. (Elsevier, 2017)
© 2016 Elsevier Inc.This research note reports upon advancements in computerization and big data creation within the off-highway plant and machinery sector. A thematic literature review synthesizes a disparate range of research initiatives and industrial developments and highlights specific examples of technological developments. A discussion regarding impact upon future employment concludes that rather than creating mass unemployment, computerization will change the employment horizon and continue to shape the global economic community. Education is quintessentially important to humanity which must master the machine and not become a slave to technology. Future proofing of educational provisions will therefore feature heavily in tomorrow's employment market. This provocative research note advances new ideas and theoretical perspectives that are specifically designed to stimulate academic debate in this novel and rapidly developing area of scientific endeavor.